Assessment of Factors Associated with Low Handwashing Coverage in Karungu Sub-County BuhweJu District. - Manigaruhanga, Pius (Kabale University, 2023)
Slow socio-demographic index (SDI) countries, unsafe water, sanitation and hygiene (W ASH) is sill the third- largest contributor to the global burden of disease at 7.8% of Disability Adjusted Life Years (DAL Ys). It is estimated that inadequate hand hygiene resulting nearly 300,000 deaths annually, with the majority of deaths being among children below 5 years old (WHO and UNICEF 2017 The study was to establish the factors associated with low hand washing coverage. It was across- sectional study that used quantitative data collection methods. The statistics in Karungu Sub-county, it experiences high prevalence of sanitation-related illnesses accounting for 67% quarterly compared to other Sub-counties closely linked to poor hand hygiene (HMIS 2018/2019). A determination of the level of knowledge. attitudes. practices. and barriers on hand washing among the respondents led to the conclusion that the respondents in the study area have sufficient knowledge about hand washing. Based on the findings, most of the respondents did not wash their hands due to lack of water. There is a need to provide piped water for easy access, promote rain water harvesting tanks and continuous sensitization on the benefits of hand washing both after use and to prevent the spread of COVID-19. Keywords: Factors, Low Handwashing, Coverage, Karungu Sub-County, BuhweJu District.